Femtosecond Laser Thermal Accumulation-Triggered Micro-/Nanostructures with Patternable and Controllable Wettability Towards Liquid Manipulating - Yin, Kai; Wang, Lingxiao; Deng, Qinwen; Huang, Qiaoqiao; Jiang, Jie; Li, Guoqiang; He, Jun (Nano-Micro Letters, 2022)
Versatile liquid manipulating surfaces combining patternable and controllable wettability have recently motivated considerable attention owing to their significant advantages in droplet-solid impacting behaviors, microdroplet self-removal, and liquid–liquid interface reaction applications. However, developing a facile and efficient method to fabricate these versatile surfaces remains an enormous challenge. In this paper, a strategy for the fabrication of liquid manipulating surfaces with patternable and controllable wettability on Polyimide (PI) film based on femtosecond laser thermal accumulation engineering is proposed. Because of its controllable micro-/nanostructures and chemical composition through adjusting the local thermal accumulation, the wettability of PI film can be tuned from superhydrophilicity ( 3.6°) to superhydrophobicity ( 151.6°). Furthermore, three diverse surfaces with patternable and heterogeneous wettability were constructed and various applications were successfully realized, including water transport, droplet arrays, and liquid wells. This work may provide a facile strategy for achieving patternable and controllable wettability efficiently and developing multifunctional liquid steering surfaces. Highlights: 1 The patternable and controllable wettability via femtosecond laser thermal accumulation engineering is proposed for liquid manipulating. 2 The wettability of polyimide film can be tuned from superhydrophilicity ( 3.6°) to superhydrophobicity (151.6 °). 3 Three diverse surfaces with patternable and heterogeneous wettability are constructed for application of water transport, droplet arrays, and liquid wells.